2008
DOI: 10.1021/ie800253u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Macroinstabilities in Single- and Multiple-Impeller Stirred Tanks

Abstract: In this work, a simplified analysis of the features of macroinstabilities in stirred tanks is proposed. The experimental part of the study is based on the collection of time series acquired by pressure transducers placed on the tank wall. The measurements are not invasive, because of the probe position, and they can be easily performed in laboratory and in industrial equipment, due to the instrumentation characteristics. With respect to previous investigations, the experimental analysis is extended from Rushto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
(131 reference statements)
3
6
0
Order By: Relevance
“…This gives f 1.1 /N = 0.020 ± 0.001 and f 2.1 /N = 0.061 ± 0.003 axially, and f 1.1 /N = 0.015 ± 0.007 and f 2.1 /N = 0.052 ± 0.015 radially. These values agree well with the precessing vortex and jet instability frequencies as reported by Paglianti et al (2008). The total MI kinetic energy, k MI,fit , reaches a maximum at y = 0 at all radial positions.…”
Section: Inter-compartment Dynamicssupporting
confidence: 89%
See 2 more Smart Citations
“…This gives f 1.1 /N = 0.020 ± 0.001 and f 2.1 /N = 0.061 ± 0.003 axially, and f 1.1 /N = 0.015 ± 0.007 and f 2.1 /N = 0.052 ± 0.015 radially. These values agree well with the precessing vortex and jet instability frequencies as reported by Paglianti et al (2008). The total MI kinetic energy, k MI,fit , reaches a maximum at y = 0 at all radial positions.…”
Section: Inter-compartment Dynamicssupporting
confidence: 89%
“…As for both phenomena frequency f scales linear with agitation rate N, MI frequencies are reported here in f/N. In the discharge stream of a 2 impeller system, frequencies of f/N ≈ 0.02 and f/N ≈ 0.055 are found for precessing vortices and jet instabilities, respectively (Paglianti et al, 2008). Guillard et al similarly identified instabilities with f/N ≈ 0.05 − 0.08 in the region above the top impeller (Guillard et al, 2000a,b).…”
Section: Multi-impeller Systemsmentioning
confidence: 87%
See 1 more Smart Citation
“…4C), with a dominant frequency f/N = 0.058 and its harmonics. This is in excellent agreement with the jet instability frequency reported by Paglianti et al (2008), and the value observed experimentally in Part I of this work. Experimentally, we also observed a weak contribution of f/N = 0.02, and strong contribution of f/N ≈ 0.04 in the parallel flow region.…”
Section: 3supporting
confidence: 93%
“…The research on MI phenomenon is of significant value for the better understanding of the flow pattern and mixing mechanism since the existence of MI help to enhance the turbulent flow to an extent, improve the mixing efficiency, moreover, it has the distinct effect on mass and heat transfer and local gas content distribution in a stirred tank [3][4]. In recent years, a number of studies have pointed to the likely effect of MI phenomenon in stirred tanks in different ways [5][6][7][8][9]. These results indicated that MI frequency is irrelevant to stirred tank size, impeller type and fluid property parameters, whereas MI frequency may produce a certain difference in condition of different Reynolds number and different ratio of kettle and impeller diameter.…”
Section: Introductionmentioning
confidence: 99%